2022
DOI: 10.1136/jitc-2021-004089
|View full text |Cite
|
Sign up to set email alerts
|

Next steps for clinical translation of adenosine pathway inhibition in cancer immunotherapy

Abstract: Increasing evidence supports targeting the adenosine pathway in immuno-oncology with several clinical programs directed at adenosine A2 receptor (A2AR, A2BR), CD73 and CD39 in development. Through a cyclic-AMP-mediated intracellular cascade, adenosine shifts the cytokine and cellular profile of the tumor microenvironment away from cytotoxic T cell inflammation toward one of immune tolerance. A perpetuating cycle of tumor cell proliferation, tissue injury, dysregulated angiogenesis, and hypoxia promote adenosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
74
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 90 publications
0
74
0
Order By: Relevance
“…Several clinical studies targeting CD39, CD73, and adenosine receptors are ongoing. Some beneficial outcomes for both mono-target therapy and combinations have been reported ( 20 , 21 ). However, the function and clinical value of ADA in cancers have not been well analyzed, including ADA1 and ADA2.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies targeting CD39, CD73, and adenosine receptors are ongoing. Some beneficial outcomes for both mono-target therapy and combinations have been reported ( 20 , 21 ). However, the function and clinical value of ADA in cancers have not been well analyzed, including ADA1 and ADA2.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we deepened these observations focusing on another key actor of the adenosinergic pathway in cancer: the A2AR ( Sitkovsky, 2020 ). Indeed, A2AR role in causing tumor immune suppression in hypoxic tumors is a consolidated notion that recently lead to several clinical trials exploring the anti-cancer therapeutic efficacy of the administration of A2AR antagonists as a stand-alone treatment or in combination with immune checkpoints inhibitors ( Boison and Yegutkin, 2019 ; Fong et al, 2020 ; Franco et al, 2021 ; Augustin et al, 2022 ). Interestingly, in the TME A2AR activation has been reported to reduce the production of those tumor eradicating cytokines IL-6, IL-17, and IFN-γ that in the present study we found downmodulated in tumor-bearing p2x7 −/− mice ( Augustin et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, A2AR role in causing tumor immune suppression in hypoxic tumors is a consolidated notion that recently lead to several clinical trials exploring the anti-cancer therapeutic efficacy of the administration of A2AR antagonists as a stand-alone treatment or in combination with immune checkpoints inhibitors ( Boison and Yegutkin, 2019 ; Fong et al, 2020 ; Franco et al, 2021 ; Augustin et al, 2022 ). Interestingly, in the TME A2AR activation has been reported to reduce the production of those tumor eradicating cytokines IL-6, IL-17, and IFN-γ that in the present study we found downmodulated in tumor-bearing p2x7 −/− mice ( Augustin et al, 2022 ). We also observed a reduction of other pro-inflammatory cytokines (IL-1β, TNF-α, and IL-12) related to P2X7R activation and, in general, to innate and type 1 immune response ( Correa et al, 2017 ; Orioli et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, A2AR role in causing tumor immune suppression in hypoxic tumors is a consolidated notion that recently lead to several clinical trials exploring the anti-cancer therapeutic efficacy of the administration of A2AR antagonists as a stand-alone treatment or in combination with immune checkpoints inhibitors (Boison and Yegutkin, 2019; Fong et al, 2020; Franco et al, 2021; Augustin et al, 2022). Interestingly, in the TME A2AR activation has been reported to reduce the production of those tumor eradicating cytokines IL-6, IL-17 and IFN- γ that we fund downmodulated in tumor-bearing p2x7 -/- mice in the present study (Augustin et al, 2022). We also observed a reduction of other pro-inflammatory cytokines (IL-1β, TNF-α and IL-12) related to P2X7R activation and, in general, to innate and type 1 immune response (Correa et al, 2017; Orioli et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we completed these observations by concentrating on another key actor of the adenosinergic pathway in cancer: the A2AR (Sitkovsky, 2020). Indeed, A2AR role in causing tumor immune suppression in hypoxic tumors is a consolidated notion that recently lead to several clinical trials exploring the anti-cancer therapeutic efficacy of the administration of A2AR antagonists as a stand-alone treatment or in combination with immune checkpoints inhibitors (Boison and Yegutkin, 2019; Fong et al, 2020; Franco et al, 2021; Augustin et al, 2022). Interestingly, in the TME A2AR activation has been reported to reduce the production of those tumor eradicating cytokines IL-6, IL-17 and IFN- γ that we fund downmodulated in tumor-bearing p2x7 -/- mice in the present study (Augustin et al, 2022).…”
Section: Discussionmentioning
confidence: 99%